EFISIENSI FAKULTAS-FAKULTAS KELOMPOK ILMU SOSIAL DI UNIVERSITAS DIPONEGORO SEMARANG - Nova Ari Astuti (Faculty of Economics and Business Diponegoro University, 2015)
The achievement of the purpose to become a superior education institute need theprovision of large resources. For it need to do measurements to assess how far theefficiency of the used of the input to the output of the specified.This research aims to measure and ranked the efficienly agroup of social sciences facultyin UNDIP semarang by using Data Envelopment Analysis (DEA). The resources becamethe input is operasional costs, internet network, the number of proffesorhod doctor andprofessor title, amount of educational worker, laboratory and library, while the outputare non academic student achievement, averoal of GPA graduates and averoal GPAwhen graduated.The result of analysis using Data Envelopment Analysis (DEA) method for during fouryears (2010-2013) shows that in general faculty of social sciences in UNDIP hasproduced output efficienthy indicated with the number of efficienthy is one. Howeverthere is on faculty that have not efficient yet, that is economics and business becauses thecost operational is to high and non academic student achievement is still low.Keywords : Faculty Efficienthy, UNDIP, Data Envelopment Analysis (DEA).